Analysis of Constitutional Court Decision No. 150/Puu-Xxii/2024 Concerning Civil Servant (PNS) Lecturers Being Advocates from the Perspective of Fiqh Siyasah - Ulong, Raja; Iwan, Iwan (IHSA Institute, 2025)
The Constitutional Court Decision No. 150/PUU-XXII/2024 allows civil servant lecturers to engage in the legal profession as advocates, strictly within the framework of community service. This study aims to examine the normative structure of both the legal profession and the civil service, analyze the content of the Constitutional Court's decision, and assess its implications from the perspective of fiqh siyasah (Islamic constitutional political jurisprudence). This research employs a normative legal method using statute, case, and conceptual approaches, supported by classical and contemporary Islamic political theory. The findings reveal normative disharmony between the Court's decision and the Law on Advocates, the Civil Service Law, and the Law on Civil Servant Discipline. Although the ruling offers individual benefit (maslahah), from the perspective of fiqh siyasah, combining the roles of lecturer and advocate contradicts the principle of separation of power (ta'addud al-mas'uliyyah) and may trigger structural disruption within public institutions. Therefore, the policy should be accepted only under strict regulatory control and institutional ethical oversight to safeguard justice, neutrality, and governance stability